Pengaruh Motivasi Kerja Dan Dispilin Kerja Terhadap Kinerja Karyawan Perusahaan X - Gulo, Sernimawati; Zebua, Dermawan (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of work motivation and work discipline on employee performance at Company X. The research employed a quantitative approach using a survey method. The population of the study consisted of all employees of Company X, with a total sample of 60 respondents selected through a saturated sampling technique. Data were collected through questionnaires developed based on the indicators of each research variable and measured using a five-point Likert scale. The collected data were analyzed using validity and reliability tests to ensure the quality of the research instrument, followed by multiple linear regression analysis with the assistance of statistical software. The results of the study indicate that work motivation has a positive and significant effect on employee performance. This finding suggests that higher levels of work motivation lead to better employee performance. In addition, work discipline also has a positive and significant effect on employee performance, indicating that employees’ compliance with organizational rules and work standards plays an important role in improving work effectiveness and productivity. Simultaneously, work motivation and work discipline have a significant effect on employee performance at Company X. The findings imply that companies should continuously enhance employee motivation through rewards, career development opportunities, and a supportive work environment, as well as strengthen work discipline through consistent and fair enforcement of organizational rules. This study is expected to contribute both theoretically and practically to the development of human resource management.